2013
DOI: 10.1093/cid/cit808
|View full text |Cite
|
Sign up to set email alerts
|

Utility of (1–3)-β-d-Glucan Testing for Diagnostics and Monitoring Response to Treatment During the Multistate Outbreak of Fungal Meningitis and Other Infections

Abstract: Our data suggest that measuring BDG in CSF is a highly sensitive test for diagnosis of fungal meningitis in this outbreak. Analysis of BDG levels in serially collected CSF demonstrated that BDG may correlate with clinical response. Routine measurement of BDG in CSF may provide useful adjunctive data for the clinical management of patients with outbreak-associated meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 20 publications
5
59
0
Order By: Relevance
“…Using this assay and a stratified sample of CSF specimens, we demonstrated that approximately 45% of the CSF specimens from case patients with negative PCR assay results had elevated levels of BDG. Our results, as well as others, also demonstrated that consistently elevated levels of BDG in CSF may indicate a relapse or persistent infection (6,7). However, because the BDG assay is not species specific, can cross-react with certain bacteria and drugs, and is prone to contamination, this test cannot be used to provide a definitive confirmation of fungal infection (6,8).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Using this assay and a stratified sample of CSF specimens, we demonstrated that approximately 45% of the CSF specimens from case patients with negative PCR assay results had elevated levels of BDG. Our results, as well as others, also demonstrated that consistently elevated levels of BDG in CSF may indicate a relapse or persistent infection (6,7). However, because the BDG assay is not species specific, can cross-react with certain bacteria and drugs, and is prone to contamination, this test cannot be used to provide a definitive confirmation of fungal infection (6,8).…”
supporting
confidence: 56%
“…Our results, as well as others, also demonstrated that consistently elevated levels of BDG in CSF may indicate a relapse or persistent infection (6, 7). However, because the BDG assay is not species specific, can cross-react with certain bacteria and drugs, and is prone to contamination, this test cannot be used to provide a definitive confirmation of fungal infection (6,8). A real-time molecular beacon PCR assay for detection of Exserohilum has also been reported (9) and used to test blood from patients with a possible association with the outbreak (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of CNS mycosis due to Exserohilum rostratum secondary to iatrogenic organism introduction, CSF ␤-glucan sensitivity and specificity were found for proven meningitis to be 96 and 95%, respectively (24). There was also some correlation of CSF ␤-glucan with a clinical response in those cases (24,25), although not a good correlation with CSF leukocyte counts, glucose, or protein. A study of cryptococcal meningitis (16) found a correlation of CSF ␤-glucan with CSF fungal burden, CSF cryptococcal antigen, and clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
“…39 Additional CSF tests to consider include β-D-glucan for Candida meningitis, mycobacterial cultures with acid-fast bacilli smear, and other tests based on the differential diagnosis (eg, polymerase chain reaction), fungal and parasitic assays (eg, Cryptococcus, Toxoplasma, Taenia), and serology and virus-detection assays. 40,41 Biochemistry of the CSF can also be helpful. CSF lactate concentration may differentiate bacterial from viral meningitis better than white blood cell count, glucose level, and protein concentration, although CSF lactate may be elevated in patients with other CNS diseases.…”
Section: Laboratory Testsmentioning
confidence: 99%